(untitled) (Journal of the College of Basic Education, 2024)
One of the reasons for choosing the topic is to try out one of the active learning strategies, which is (the Socratic Circle), which works to consolidate the roles of students in educational situations as they are the pillar around which the learning process revolves. It is based on free, constructive dialogue and exchange of information, thus developing higher-order thinking skills. The researcher aims to know the effectiveness of the Socratic circle strategy in achieving the course of specialized teaching methods among students of the College of Basic Education and their achievement motivation. The research sample consisted of (75) male and female students from the College of Basic Education, fourth stage, The unstructured method was used in determining The students of Section (B) were chosen for the experimental group, numbering (38) male and female students, and they studied it using the Socratic Circle strategy, and the students of Section (C) were selected for the control group, numbering (37), and studied it in the usual way. The researcher rewarded the two groups statistically in terms of previous information and intelligence. The researcher developed two null hypotheses, including In their achievement and achievement motivation, the researcher used an experimental design. The researcher prepared two tools, the first: an achievement test in the specialized teaching methods course, which consisted of (20) items, and the second: a measure of their achievement motivation, which consisted of (30) items. Their validity and reliability were verified. After the end of the experiment period, the researcher applied the two research tools to the two research groups. Then, after collecting the data he obtained, he processed the data using appropriate statistical methods and reached the following results: The students of the experimental group outperformed the students of the control group in the achievement test and their measure of achievement motivation.